Ageing alters the severity of Sunitinib-induced cardiotoxicity: Investigating the mitogen activated kinase kinase 7 pathway association. (1st January 2019) - Cooper, Samantha; Sandhu, Hardip; Hussain, Afthab; Mee, Christopher; Maddock, Helen
Abstract: Anti-cancer drug Sunitinib is linked to adverse cardiovascular events, which have shown to involve mitogen activated kinase kinase 7 (MKK7) pathway. Sunitinib-induced cardiotoxicity in 3, 12 and 24 months old male Sprague-Dawley rats and MKK7 expression and activation was investigated using the Langendorff perfused heart model followed by Western blot analysis. Cardiac function and infarct size were measured during/after 125 min of Sunitinib treatment. Left ventricular cardiac samples were analysed by qRT-PCR for expression of MKK7 mRNA and cardiac injury associated microRNAs. Infarct size was increased in all Sunitinib treated age groups. Haemodynamic alterations were observed following Sunitinib administration. Left ventricular developed pressure (LVDP) was decreased in all age groups, while heart rate (HR) was decreased in 3 and 12 months groups. Sunitinib treatment decreased the expression of miR-27a in all age groups, while miR-133a and miR-133b levels were increased in 3 months and decreased in 24 months groups. MKK7 mRNA and p-MKK7 levels were decreased in the 3 months group after Sunitinib treatment. MKK7 mRNA level was increased in 24 months group and p-MKK7 levels were increased in 12 months group following Sunitinib treatment. This study highlights the importance and impact of ageing and anti-cancer therapy-induced cardiotoxicity.